First Records of Talon Cusps on Baboon Maxillary Incisors Argue for Standardizing Terminology and Prompt a Hypothesis of Their Formation. Issue 12 (31st October 2013) - Heaton, Jason L.; Pickering, Travis Rayne
ABSTRACT Dental characters can provide vital clues for understanding intra‐ and intertaxonomic morphological variation and its underlying genetic and environmental components. However, the unambiguous identification of particular traits and their comparative study is often confounded by lack of consistent terminology in the relevant literature. This difficulty is exacerbated when the etiologies are not completely understood, as is the case with talon cusps. To date, research on talon cusps has focused on modern humans. In many instances, descriptions of talon cusps appear in clinical case studies focusing on their treatment and removal. What is lacking in those discussions, though, is a comparative framework, in which the occurrence of talon cusps in nonhuman primates, and possibly other mammals, is established and understood. Here, we report on a taloned upper central incisor of a wild baboon (Papio hamadryas ursinus) from South Africa. The anomalous incisor of this individual includes an exaggerated accessory cusp diagnosed as a Type II talon. Microcomputed tomographic and radiographic analyses show that the taloned cusp possesses enamel, dentin, and pulp. In addition, we identified an unclassifiable talon cusp on a central maxillary incisor of a baboon skull housed in the Smithsonian Institution's Natural History Museum collection. Our observations of talon cusps on baboon incisors demonstrate that, with regard to this phenomenon, systematic study of nonhuman primates is much needed, along with a consistent use of terminology in the anatomical and anthropological literature. Finally, we present a hypothesis of the formation of talon cusps on mammalian incisors. Anat Rec, 296:1874–1880, 2013. © 2013 Wiley Periodicals, Inc.